Musculoskeletal pain is common in competitive gaming: a cross-sectional study among Danish esports athletes - Lindberg, L.; Bay Nielsen, S.; Damgaard, M.; Rolskov Sloth, O.; Skovdal Rathleff, M.; Lund Straszek, C. (BMJ Open Sport & Exercise Medicine, 2020)
Objectives The interest for competitive esports is growing. Little is known regarding musculoskeletal (MSK) pain among esports athletes. We aimed to investigate (1) the prevalence of MSK pain, (2) the association between MSK pain and esports-related training volume and (3) the association between MSK pain and physical activity levels.